Analisis Kemampuan Pemecahan Masalah Matematis Siswa pada Pembelajaran Inkuiri Terbimbing dengan Pendekatan CRA - Afri, Lisa Dwi (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This study aims to describe students' mathematical problem solving abilities after undergoing inquiry learning with Concrete-Representational-Abstract approach (IT-CRA). This research is a mix method research. The subjects are students of class VIII-B SMPN 1 Padang Panjang, academic year 2015/2016 about 34 people, taken by purposive sampling. The data was collected by test of mathematical problem solving skills and interview. The data of this research consist of qualitative that’s postes and quantitative that’re pretest and postes score. Analysis of qualitative data was in three stages, namely data reduction, data presentation, and conclusion. Analysis of quantitative data was to determine the percentage of student achievement based on protest score, and n-gain score to see the great improvement of students' mathematical problem solving abilities after IT-CRA learning. The results showed that the achievement rate was 66,67% in good enough category. Based on KAM, the achivement of student with high KAM is 85.64% (good), medium KAM is 66.80% (good enough), and low KAM is 47.22% (not good). Furthermore, the average scores of n-gain obtained by 0.61 in the medium category. Then, averages of n-gain on each KAM are moderate. Based on the analysis of postes answers, it is concluded that most students have been able to use strategy of problem solving. However, only a small percentage of students re-check the answer.